Energy Transition and Environmental Sustainability - Pearce, Prafula (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Energy transitions and environmental sustainability does not occur overnight as it may take years of policy debates both from within domestic jurisdictions and from international organisations. It often requires energy saving technology innovations to drive appropriate investment decisions that can then allow energy transition to occur. There is no one global solution. Countries progress in their energy transition goals by taking small steps as demonstrated in this special issue, “Energy Transition and Environmental Sustainability”. This Special Issue provides thirteen interesting papers showing examples of projects undertaken or challenges encountered in various countries, such as: Legal reforms for energy transition in Taiwan and Japan; Transition towards solar PV in South Korea; Transition to electricity driven buses in Central Europe; Vehicle transition and the development of electric car production in the United States, the European Union and Japan; Cooling solutions for buildings in Pakistan; Projects in Ecuador to replace fossil fuel use with Hydropower; The Role of Electrification in the Decarbonization of Central-Western Europe; Energy technology innovation through the application of new technologies in oil resource development; Wastewater treatment challenges in Poland; Increased climate change litigation facing Australian Energy Companies; Renewable energy solution to a Childcare facility in Tokyo; and Canadian policies to support renewable gas production from organic waste. This Special Issue provides global perspectives and uncertainties on energy transition and will appeal to all levels of readers.